Evaluasi Pembelajaran Daring Mata Kuliah Rangkaian Listrik di Jurusan Teknik Elektro Universitas Negeri Padang - Viona Permata Sari Eriska; Riki Mukhaiyar (Jurnal Pendidikan Teknik Elektro, 2022)
This research was motivated by the application of online learning due to COVID-19, changes in the way of learning which resulted in the learning process that was originally carried out on campus into distance learning (online). Students who are accustomed to doing face-to-face learning must be faced with the reality of learning online through existing online media. To find out the ongoing online learning in the electrical engineering department of FT-UNP, one way that can be done is to evaluate the online learning that has taken place. This study aims to evaluate online learning in electrical circuit courses in the electrical engineering department of FT-UNP using the CIPP (Context, Input, Process, Input) evaluation model. This study uses qualitative research methods with descriptive evaluative data and data analysis according to Miles and Hubberman. Data collection techniques using interviews and documentation. The results of the study concluded that the Semester Lesson Plan used in online learning for electrical circuit courses using the CIPP evaluation model (Context, Input, Process, Input) as a whole was appropriate. Based on interviews about the online learning process, the results showed that the evaluation of online learning for electrical circuit courses was effective for learning during the spread of COVID-19, so the learning was continued with preparation needed between students and lecturers regarding online learning procedures. From these results, it can be concluded that the implementation of the learning process in the online electrical circuits course in the electrical engineering department, FT UNP, has been carried out well according to the Semester Learning Plan standards and the recommendations given in the electrical circuits course should be carried out in a blended learning manner to maximize analytic learning. calculations cannot be done online so the learning is carried out offline.